Respuesta :

Answer: y= -2.5

Step-by-step explanation:

Distribute the -2 and 3 into the parentheses. -6 + 6 cancels out so you are left with 3y on the right side. Add 2y to the right side leaving you with -2=5y. Divide both sides by -2

Answer:

[tex] \boxed{ \bold{ \boxed{ \sf{ y = - 0.4}}}}[/tex]

Step-by-step explanation:

[tex] \sf{ - 2(y + 1) = 3(y - 2) + 6}[/tex]

Distribute -2 through the parentheses

Similarly, Distribute 3 through the parentheses

⇒[tex] \sf{ - 2y - 2 = 3y - 6 + 6}[/tex]

Since two opposites add up to zero , remove them

⇒[tex] \sf{ - 2y - 2 = 3y}[/tex]

Move 3y to Left hand side and change it's sign

Similarly, move -1 to right hand side and change it's sign

⇒[tex] \sf{ - 2y - 3y = 2}[/tex]

Collect like term

⇒[tex] \sf{ - 5y = 2}[/tex]

Divide both sides of the equation by -5

⇒[tex] \sf{ \frac{ - 5y}{ -5 } = \frac{2}{ - 5} }[/tex]

Calculate

⇒[tex] \sf{ - 0.4}[/tex]

Hope I helped!

Best regards!